Mechanical Performance of Plywood Bonded with Castor Oil-based Polyurethane Resin Enhanced by Nanocellulose - Luana Cristal Lirya Silva; Sandro de Souza Monteiro Filho; Felipe Oliveira Lima; Cristiane Inácio de Campos (Materials Research, 2025)
The study of engineered wood products has expanded due to their production from renewable raw materials. While wood products have traditionally seen limited use in Brazil, they have gained significant traction over the past two decades, fueled by new products and technological advancements. Among emerging materials, nanocellulose has shown promise due to its potential to enhance the adhesive performance and mechanical properties of wood-based panels. This study aimed to incorporate cellulose nanofibers obtained by mechanical defibrillation of pulp from the extraction of the Eucalyptus grandis by kraft process in proportions of 0% and 5% into a castor oil-based polyurethane adhesive commercial to produce plywood panels. The mechanical properties of the panels were analyzed, specifically focusing on static bending strength both parallel and perpendicular to the wood fibers, as well as bond quality through shear testing along the glue line. Results indicated that adding nanocellulose to the polyurethane resin significantly enhanced the mechanical performance of the plywood panels. Additionally, it was observed that using eucalyptus wood veneers with polyurethane resin alone already resulted in improved mechanical properties compared to conventional adhesives. Thermal analysis, suggested that nanocellulose incorporation increased the resin's thermal stability, potentially contributing to enhanced durability. Further studies are recommended to explore the viability of nanocellulose at different proportions and its long-term effects on adhesive performance.